Poisonous Plants and Related Toxins 2003
DOI: 10.1079/9780851996141.0175
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial properties of phytochemicals in aromatic plants in poultry diets.

Abstract: A study was conducted to evaluate the effect of herbal supplementation of broiler diets on some prevalent species of gut microbes. Ninety day-old broiler chicks were randomly grouped into five cages for 29 days. The birds were fed a basal wheat/soyabean meal ration. Each cage was randomly assigned to one of six dietary treatments. Oregano, marjoram, thyme, yarrow or rosemary were added as dried herb material to the basal diet, with the 6th treatment acting as control. There was no effect of treatment on the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2005
2005
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…Thymol has been shown to reduce the numbers of coliforms within the digesta from chickens from about 1·10 10 /g to about 1·10 8 . 5 /g (Cross et al 2004). Thymol has also been demonstrated to reduce fermentation by micro-organisms from the GIT in chickens (Shanmugavelu et al 2004), although other work has demonstrated little effect of a mixture of essential oil components (Lee et al 2003).…”
Section: Essential Oilsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thymol has been shown to reduce the numbers of coliforms within the digesta from chickens from about 1·10 10 /g to about 1·10 8 . 5 /g (Cross et al 2004). Thymol has also been demonstrated to reduce fermentation by micro-organisms from the GIT in chickens (Shanmugavelu et al 2004), although other work has demonstrated little effect of a mixture of essential oil components (Lee et al 2003).…”
Section: Essential Oilsmentioning
confidence: 99%
“…However, more recently, the beneficial effects of PSM in animals (and man) have also been investigated (Douglas et al 1995;Kinghorn & Kennelly, 1997;Pfannhauser et al 2001;Cross et al 2004;James et al 2004;Nash, 2004;Bento et al 2005). A classic example of a compound that was initially considered as problematic when consumed by animals is mimosine.…”
Section: Phytochemicals: Effects In Animalsmentioning
confidence: 99%
“…However, although the antibacterial activity of thyme has been demonstrated in many destinations, the purpose of the recent study is to evaluate the use of thyme in poultry diet as a reducing agent of E. coli population in gastrointestinal system as well as the possible improvement of growth indices and meat contamination reduction. Concerning thyme effects on the gastrointestinal microflora, few reports are available (21,26). Cross et al (26) showed that thymol as essential oil extracted from thyme can significantly reduce the total number of coliform bacteria in the gastrointestinal tract.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning thyme effects on the gastrointestinal microflora, few reports are available (21,26). Cross et al (26) showed that thymol as essential oil extracted from thyme can significantly reduce the total number of coliform bacteria in the gastrointestinal tract. Also, Tschirch (21) stated that carvacrol as one component of thyme essential oil had a positive effect on the growth and proliferation of intestinal lactobacillus species.…”
Section: Discussionmentioning
confidence: 99%
“…The beneficial effects of garlic in the diet are evident and may indicate an antimicrobial effect in vivo. However, longer periods of dietary garlic inclusion (>10-20d) may affect the meat flavour as a strong odour was detectable in the hens [Cross et al, 2004].…”
Section: Antiviral Propertiesmentioning
confidence: 99%